ANALISIS KETINGGIAN TOOL PUNCH RIVET TERHADAP HASIL RIVET ING CONTACT PADA SWITCH LAMPU REM MOTOR TIPE C8EA - Cuncun -; Paridawati -; Taufiqullah - (Jurnal Ilmiah Teknik Mesin, 2020)
The product of CBEA Terminal B / B2 Assy is one of the C8EA type Switch components used for brake light switches on two-wheeled vehicles. In the manufacturing process often experience Contact Crack. Contact Crack problems occur in the rivet ing process. This study aims to reduce / eliminate the contact Crack problem, the method used is to conduct research on variations in the height of the punch in the rivet ing process. The initial height of the punch before the research is 49.10 mm, in this study the height of the punch to be examined is 48.60 mm, 48.70 mm, 48.80 mm, 48.90 mm and 49.00 mm. The results obtained for the most appropriate punch height are the height of 48.60 mm with the contact Crack ratio of 3/20, the size of the Crack & contact size entered into the standard, the flexural strength is still standard and the average hardness produced is 92.52 HV which is included in the maximum standard.